Inequality in South Africa: a possible solution within the labour market - Ferreira, John-Edward (Rhodes University, Faculty of Commerce, Department of Economics, 2016)
This study sets out to identify the most effective way in which persistently and unacceptably high levels of inequality can be reduced in South Africa. Three alternative approaches were identified from the literature and their impact explored statistically. They are: the introduction of a 'Social Solidarity Grant'; a decrease in unemployment by 5%; and a narrowing of the skill premium through an expansion of tertiary education. It is important to note that the study makes no attempt at explaining how these outcomes might be implemented or achieved. Rather, it sets out to determine only the effect that such policies may have on measured inequality. It was found that while the introduction of a new grant had a significant effect on inequality, this effect however, was once-off. The grant would be financed by individuals in the top decile through tax increases, which would be a complicated endeavour. Both job creation and a narrowing of the skills premium were significantly effective in decreasing inequality. The narrowing of the skills premium showed more promise due to its accelerating effectiveness in decreasing inequality over time and the fact that it directly addresses the problem of wage differentials. It was noted that the extreme levels of poverty and unemployment in South Africa may dampen enthusiasm for policies that narrow the skills premium to reduce inequality. These characteristics make job creation a more popular policy option because of the positive impact on poverty and unemployment as well as on inequality.
Keywords: Uncatalogued